Exploring Coping Strategies Among Indonesian Adolescents Diagnosed with Bipolar Disorder: A Qualitative Case Study - Aulia Nur Setyaningrum; Arthur Huwae (Da'wa Faculty of Islamic State University Salatiga, 2025)
Bipolar disorder is a psychological disorder that can affect mental health and cause extreme mood swings. Coping strategies that focus on problem-solving and reducing or managing emotional stress are needed. This study aims to explore coping strategies among individuals diagnosed with Bipolar disorder using a qualitative approach with a case study design. The participants in this study consisted of four individuals aged 17-25 years with Bipolar disorder, selected using purposive sampling. Data were collected through semi-structured interviews and analyzed using the interactive analysis technique by Miles and Huberman. The results of the study indicate that participants employ coping strategies such as taking medication regularly, counseling, engaging in favorite activities, pursuing hobbies, and exercising. Additionally, support from partners, family, and friends plays a crucial role in helping participants cope with bipolar disorder. Cultivating self-love through positive self-affirmation and seeking spiritual support through prayer and gratitude can also serve as coping strategies. Factors contributing to bipolar disorder include traumatic experiences in the past, such as limited social contact during COVID, domestic violence during childhood, broken homes, and toxic relationships. This study provides insights into the dynamics of individuals diagnosed with bipolar disorder and the coping strategies used by individuals diagnosed with bipolar disorder.